Biophysical approach to the problem of safety of diagnostic ultrasound - HRAZDIRA, Ivo (Archives of Acoustics, 1984)
Every application of the ultrasonic technique in medical diagnostics involves the deposition of energy in tissues which can lead to some biological effects. The dependence of biological effects on physical characteristics of the ultrasonic field is often nonlinear. On the one hand, most of the mechanical factors of ultrasound are nonlinearly related to both the intensity and the frequency. On the other hand, the metabolic and regulatory processes of a given biological subject cause its nonlinear response to ultrasonic action. The nonlinearity increases with increasingly higher level of biological organisation. The biophysical approach to the problem of safety of diagnostic ultrasound consists in detailed assessment of relations between the acting ultrasonic impulse and the registered alteration of the biological system.